(2x+9/5)-(2x-11/2)=(2x+8/3)-5

Simple and best practice solution for (2x+9/5)-(2x-11/2)=(2x+8/3)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+9/5)-(2x-11/2)=(2x+8/3)-5 equation:


x in (-oo:+oo)

2*x-(2*x)+9/5+11/2 = 2*x+8/3-5 // - 2*x+8/3-5

2*x-(2*x)-(2*x)+9/5+11/2-(8/3)+5 = 0

2*x-2*x-2*x+9/5+11/2-8/3+5 = 0

289/30-2*x = 0 // - 289/30

-2*x = -289/30 // : -2

x = -289/30/(-2)

x = 289/60

x = 289/60

See similar equations:

| 2x^2-13x-31=0 | | 2x^2-13-31=0 | | (2x+3/5)-(2x-11/2)=(2x+8/3) | | 105/7.5 | | p^2=7p | | x+(x/100)*14=y | | x+x/100*14=y | | (-8/2u+6)+2=(-4/u+3) | | 16m-3=48 | | x1/3.9/y | | factor-60x+225=0 | | 3x+25=5x-13 | | 116-6x=2x+11 | | Lgx=4 | | (-14)-3x=11-8x | | 9-8x=4x-5 | | 12-3x=4x-9 | | (1/3)(2x-3(8x+3)+2(6x-1))=x-8 | | 297=x+2*x*3 | | (6y^2-19y-15)=0 | | 4x+13=6x-3 | | 5(x)=8-x | | 5-3(x)=25 | | 7x^2+2=0x-9 | | y=200+0.8Y+300 | | (6x)/(x+4)(x-4)/(x-4) | | y=200+0.8Y+300+100 | | x^2=(8/9)x | | Y=100+.75(Y-100)+200+100 | | 3x+5(x-4)=4x+8 | | Y=200+0.8(Y-100)+300+100 | | 3x-18=x+8 |

Equations solver categories